DAMAGE OF RENAL FUNCTION AND DYNAMICS OF DYSLIPIDEMIA IN PATIENTS WITH TYPE 2 DIABETES MELLITUS WITH INSUFFICIENT GLYCEMIC COMPENSATION UNDER CONDITION OF CORRECTION OF HYPERTENSION WITH ANGIOTENSIN II RECEPTOR ANTAGONISTS - N.O. Pertseva (Ukrainian Journal of Nephrology and Dialysis, 2014)
Damage of renal function and dynamics of dyslipidemia in patients with type 2 diabetes mellitus with insufficient glycemic compensation under condition of correction of hypertension with angiotensin II receptor antagonists Introduction. Need to be studied issues related to the dynamics of nephropathic and dyslipidemic disorders on the background of long-term treatment of hypertension with using angiotensin II receptor antagonists in patients with type 2 diabetes mellitus. Materials and methods. The treatment and examination of 87patients with type 2 diabetes mellitus with insufficient glycemic compensation and hypertension. The dynamics of nephropathic and dyslipidemic disorders during 1 year of treatment was studied. Results and discussion. On the background of the standard treatment of hypertension occur regression of microalbuminuria in 32.3% of patients, as well as normalization of concentrations of low density lipoprotein cholesterol and triglyceride levels after 1 year of treatment. Antihypertensive therapy with the use of angiotensin II receptor antagonists significantly more effective than standard treatment policy to influence the development of dyslipidemia.Conclusion. After 6 months of treatment on the background of normalization dyslipidemic disorders and nephropathic disorders use ofangiotensin II receptor antagonists followed by regression of microalbuminuria in 54.7% ofpatients.